Community-Based Social Entrepreneurship In Clean Water Management In Gudang Garam Village, Bintang Bayu Sub-district, Serdang Bedagai District - Viola Asti Lestari (Talenta Publisher, 2023)
The theory of social entrepreneurship is used in analyzing and looking at the phenomena that occur in the development pattern of gudang garam village. Can be seen in four aspects of social entrepreneurship. The first social value, with social benefits, is donating the profits obtained for the benefit of the community. The social mission continues to try and strive to get clean water, and social entrepreneurship opportunities are used as development assets, and there are purchases for clean water users. Second, the civil society originated from the village government's initiative to form BUMDES to increase and develop BUMDES businesses. Community participation by cooperation and self-help in damages, social media used to promote businesses, namely the youtube and Facebook websites. The three innovations, namely adding value to the village government, continue to advance their water management potential and open jobs to make the product superior. Finally, economic activity is engaged in entrepreneurial activities facilitating the community and continuing to be creative in developing its business product; the distribution of businesses profits that are owned is very promising in the long term and makes the community prosperous.